1984
DOI: 10.1128/mcb.4.5.985
|View full text |Cite
|
Sign up to set email alerts
|

5-Methylcytosine is not detectable in Saccharomyces cerevisiae DNA.

Abstract: We examined the DNA of Saccharomyces cerevisiae by both HpaII-MspI restriction enzyme digestion and high-performance liquid chromatography analysis for the possible presence of 5-methylcytosine. Both of these methods failed to detect cytosine methylation within this yeast DNA; i.e., there is <1 5-methylcytosine per 3,100 to 6,000 cytosine residues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
98
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(101 citation statements)
references
References 17 publications
2
98
1
Order By: Relevance
“…In fungi, m5C is concentrated in repeat loci whereas active genes are not methylated 6,9 . Furthermore, several model eukaryotes are devoid of DNA methylation altogether, including the yeast Saccharomyces cerevisiae 12 , the nematode Caenorhabditis elegans 13 , the fruit fly Drosophila melanogaster 14 (except in the early stages of embryogenesis 15 ) and the brown alga Ectocarpus siliculosus 16 . From the methylomes examined thus far, it is therefore unclear which are the ancestral underlying mechanisms at work and those that have been co-opted to distinct biological roles in different eukaryotic groups.…”
mentioning
confidence: 99%
“…In fungi, m5C is concentrated in repeat loci whereas active genes are not methylated 6,9 . Furthermore, several model eukaryotes are devoid of DNA methylation altogether, including the yeast Saccharomyces cerevisiae 12 , the nematode Caenorhabditis elegans 13 , the fruit fly Drosophila melanogaster 14 (except in the early stages of embryogenesis 15 ) and the brown alga Ectocarpus siliculosus 16 . From the methylomes examined thus far, it is therefore unclear which are the ancestral underlying mechanisms at work and those that have been co-opted to distinct biological roles in different eukaryotic groups.…”
mentioning
confidence: 99%
“…In addition, two environments (cCg and tCg) show additional elevations in mutation rate. (39)(40)(41). However, a recent study using air chromatography found ∌0.364% methylation at cytosines in S. cerevisiae (42).…”
Section: Discussionmentioning
confidence: 99%
“…Although DNA methylation at CpG dinucleotides is a general phenomenon of eukaryotic genomes, methylated CpG residues have not been found in several well-known genetic model systems, such as the yeast, C. elegans, and Drosophila (23)(24)(25). Evidence for expression of CpG MTase(s) in these organisms also has been lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the vertebrates, the genomes of Drosophila, Caenorhabditis elegans, and yeast are deficient in m 5 C residues, at least at the resolution level of HPLC analyses (23)(24)(25). Evidence for the existence of CpG MTase-like proteins in these organisms also is lacking (see Discussion).…”
mentioning
confidence: 99%